Circulating exosomal microRNAs as potential biomarkers of hepatic injury and inflammation in a murine model of glycogen storage disease type 1a - Roberta Resaz; Davide Cangelosi; Martina Morini; Daniela Segalerba; Luca Mastracci; Federica Grillo; Maria Carla Bosco; Cristina Bottino; Irma Colombo; Alessandra Eva (The Company of Biologists, 2020)
Most patients affected by glycogen storage disease type 1a (GSD1a), an inherited metabolic disorder caused by mutations in the enzyme glucose-6-phosphatase-α (G6Pase-α), develop renal and liver complications, including the development of hepatocellular adenoma/carcinoma. The purpose of this study was to identify potential biomarkers of the pathophysiology of the GSD1a-affected liver. To this end, we used the plasma exosomes of a murine model of GSD1a, the LS-G6pc−/− mouse, to uncover the modulation in microRNA expression associated with the disease. The microRNAs differentially expressed between LS-G6pc−/− and wild-type mice, LS-G6pc−/− mice with hepatocellular adenoma and LS-G6pc−/− mice without adenoma, and LS-G6pc−/− mice with amyloidosis and LS-G6pc−/− mice without amyloidosis were identified. Pathway analysis demonstrated that the target genes of the differentially expressed microRNA were significantly enriched for the insulin signaling pathway, glucose and lipid metabolism, Wnt/β-catenin, telomere maintenance and hepatocellular carcinoma, and chemokine and immune regulation signaling pathways. Although some microRNAs were common to the different pathologic conditions, others were unique to the cancerous or inflammatory status of the animals. Therefore, the altered expression of several microRNAs is correlated with various pathologic liver states and might help to distinguish them during the progression of the disease and the development of late GSD1a-associated complications.